Identification of rare nonsynonymous variants in SYNE1/CPG2 in bipolar affective disorder. (June 2017) - Sharp, Sally I.; Lange, Jenny; Kandaswamy, Radhika; Daher, Mazen; Anjorin, Adebayo; Bass, Nicholas J.; McQuillin, Andrew
Abstract : Background: Bipolar affective disorder (BPD) is a severe mood disorder with a prevalence of ∼1.5% in the population. The pathogenesis of BPD is poorly understood; however, a strong heritable component has been identified. Previous genome-wide association studies have indicated a region on 6q25, coding for the SYNE1 gene, which increases disease susceptibility. SYNE1 encodes the synaptic nuclear envelope protein-1, nesprin-1. A brain-specific splice variant of SYNE1, CPG2 encoding candidate plasticity gene 2, has been identified. The intronic single-nucleotide polymorphism with the strongest genome-wide significant association in BPD, rs9371601, is present in both SYNE1 and CPG2 . Methods: We screened 937 BPD samples for genetic variation in SYNE1 exons 14–33, which covers the CPG2 region, using high-resolution melt analysis. In addition, we screened two regions of increased transcriptional activity, one of them proposed to be the CPG2 promoter region. Results and Conclusion: We identified six nonsynonymous and six synonymous variants. We genotyped three rare nonsynonymous variants, rs374866393, rs148346599 and rs200629713, in a total of 1099 BPD samples and 1056 controls. Burden analysis of these rare variants did not show a significant association with BPD. However, nine patients are compound heterozygotes for variants in SYNE1 / CPG2, suggesting that rare coding variants may contribute significantly towards the complex genetic architecture underlying BPD. Imputation analysis in our own whole-genome sequencing sample of 99 BPD individuals identified an additional eight risk variants in the CPG2 region of SYNE1 . Abstract : Supplemental Digital Content is available in the text.